A Needs Analysis for Developing the Project-Task Based Learning (PROTABING) Model in Indonesian Language Instruction - Jasmienti, Jasmienti; Indriyani, Vivi; Rahmayani, Rizka Dwi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
This study aims to analyze the need for developing a Project-Task Based Learning (PROTABING) poetry learning model in senior high schools to address the challenges of Indonesian language learning. Using a descriptive qualitative approach with a focus on needs analysis, this study involved 71 tenth-grade students and two Indonesian language teachers in Bukittinggi selected through purposive sampling. Data were collected through questionnaires, semi-structured interviews, and document analysis of learning tools using a checklist. The study findings revealed specific student barriers, including difficulty interpreting metaphorical meanings (88%), confusion in the use of figurative language (90.5%), and low self-confidence in oral appreciation (89%). Meanwhile, the analysis of the tools showed that although the teaching module had met administrative standards, the available evaluation instruments were not yet able to authentically measure higher-order thinking skills (HOTS). On the other hand, the majority of students' learning motivation was in the moderate category (67%), indicating the need for a more challenging learning model. These results confirm the urgent need for a PROTABING model that can systematically bridge tasks with projects. The implications of this research emphasize that reforms to Indonesian language learning models must integrate differentiation aspects to accommodate diverse student characteristics. Further research is needed to determine the validity, practicality, and effectiveness of the PROTABING model, both on a limited and broader scale.